Análisis cefalométrico de tejidos blandos de Arnett en estudiantes de Tercer Año de Bachillerato del colegio Adolfo Valarezo de la ciudad de Loja, periodo marzo-julio 2016. - Benavides Guaricela, María Isabel (2016)
The study presented hereby is quantitative, prospective, descriptive, observational and cross-sectional type. The objective was to determine the values of the Soft Tissue Arnett Cephalometric Analysis of from a sample of mixed-race individuals and compare these values with the Caucasian standardized measures, to establish if there are significant differences. The analyzed population in this research work was formed by 40 people, 22 males and 18 females, between 17 and 19 years old, students of the senior high school year of “Adolfo Valarezo” High School, from the city of Loja. For the Arnett Analysis, photos of the participants’ faces were necessary; which were printed in actual size, with high quality, and the analysis was developed using cephalometric paper and a cephalometric ruler. The results were processed using the SPSS Statistics software package, version 24.0, through a comparative study of the average values of a population with the normal values. The analysis values were obtained and it was proven that there are differences between the values found and the ones proposed by Arnett; these can be attributed to the dissimilar craniofacial morphology between races or ethnic groups. It was concluded that the differences are stronger in the following values: profile angle, nasal projection and Subnasal-Pogonion lower lip line. Key Words: Analysis, Soft Tissues, Arnett Analysis.